Investigating the Physical Properties of Dusty Star-forming Galaxies at z ≳ 1.5 in the GOODS-South Field Using JWST - Dipanjan Mitra; Mattia Negrello; Gianfranco De Zotti (The Astrophysical Journal)
We investigated how well the physical properties of progenitors of present-day massive spheroidal galaxies (protospheroids) can be constrained by the JWST Advanced Deep Extragalactic Survey (JADES) in the GOODS-South field, which benefits from extensive photometric and spectroscopic data, including those from the Hubble, Spitzer, and Herschel. We adopted a physical model for the evolution of protospheroidal galaxies, which form the bulk of dusty star-forming galaxies (DSFGs) at z  ≳ 1.5 and confirmed its consistency with recent mid-infrared high- z galaxy luminosity functions. Using the model and the JADES survey strategy, we simulated a sample of protospheroids over 87.5 arcmin ^2 , matching the JADES/GOODS-S survey area. Photometric redshifts estimated from simulated JWST photometry showed ≳95% accuracy and were used in spectral energy distribution fittings with Code Investigating GALaxy Emission (CIGALE). We demonstrated that JWST will provide reliable stellar mass estimates up to 0.1 dex for the majority of protospheroids at z  ≳ 1.5 and can detect low-mass systems during cosmic noon that were inaccessible in the pre-JWST era. Focusing on the active star-forming phase of the protospheroid evolution, we defined a subsample flux limited at 250 μ m (DSFG sample) and derived star formation rate, dust luminosity, and dust mass complementing the JWST photometry with that from Spitzer/MIPS and Herschel. We also constructed a JWST-selected DSFG catalog from ASTRODEEP data using NIRCam color criteria and demonstrated strong consistency between the observed and simulated DSFG populations.